Management model for the application of lean manufacturing tools to reduce returns of incorrect orders in a pharmaceutical company - Carrillo Quezada, Melina Nadel (2025)
The research seeks to apply lean manufacturing tools to reduce returns of wrong orders, the main problem that affects the company under study, which is a pharmaceutical company. For which it will begin by developing a value stream mapping that determines the waste and the Lean tools to use (5S, SMED and Kaizen). Data analysis was done using inferential statistical techniques, with the objective of testing the proposed hypotheses. For this, an evaluation was carried out to measure reliability and normality. After the application of various improvement tools, each result obtained from January to December 2023 was evaluated. The final result was that the percentage of returns of incorrect orders decreased from 14 % to 7 %. It was concluded that the adoption of Lean tools generated significant advantages for the company, ranging from the detection of inefficiencies, standardization to continuous improvement.